Ethics Of Entrepreneurship In The Context Of The Sociocultural Process Of A Reforming Society - Hasanova Rayhon Bozorovna (Periodica Journal, 2024)
Article deals with a holistic ethical and philosophical analysis of business and entrepreneurship in the light of modern ethical theories. The article also uses a textual analysis of primary sources - the classical texts of Western European thinkers and classical religious philosophers. Along with the general logical and philosophical analysis of the problem presented in classical theories, the work uses the results and methods of modern theoretical research, primarily in the field of business ethics. To reconstruct the central meanings of the studied phenomenon, the data of linguoetymological analysis were used.
Keywords: phenomenon; methods; general; primary